From the Luxembourg Agreement onwards: Antisemitism and the Normative Trajectory of German Law - Pacurar, Anna (State and Law, 2026)
This article examines how normative logic embedded in reparations law continues to shape contemporary German criminal law, taking the Luxembourg Agreement of 1952 between the Federal Republic of Germany, the State of Israel and the Jewish Conference on Material Claims against Germany (JCC) as its very conceptual point of departure. Against the backdrop of rising antisemitic criminal offenses in Germany, the article focuses on the amendment of Section 46 (2) of the German Criminal Code (StGB; Strafgesetzbuch), which explicitly includes antisemitic motives among the circumstances relevant for sentencing. While this amendment has been criticized as merely declaratory or even ‘symbolic’, this article argues that such criticism overlooks the deeper legal genealogy of state responsibility that ultimately originates in the Luxembourg Agreement. Antisemitic motives intensify culpability and wrongfulness because they engage the foundational commitments of the post-war legal order that emerged in response to antisemitic state-driven violence. Explicitly naming such motives in sentencing law therefore constitutes a crucial institutional function by shaping investigative practices, judicial reasoning, and normative expectations within the criminal justice system. From a criminal legal perspective, the article develops an account of motives as normative indicators that affect both culpability and wrongfulness. Antisemitic motives, it argues, intensify the Unrechtsgehalt of an offense because they negate the equal moral status of the victim and symbolically attack the legal order that emerged in response to antisemitic state violence. The article concludes that the explicit inclusion of antisemitic motives in Section 46 (2) StGB reflects a coherent and legally grounded response to historically specific injustice and underscores the role of criminal law in stabilizing responsibility within the German legal order.